El juego infantil y su metodología en los estudiantes de educación básica elemental - Torres Torres, Valeria Estefania (2024)
This research work, titled "Children's game and Its Methodology in Elementary Education Students," is an activity of fun, entertainment, and satisfaction that demonstrates joy; being pleasurable promotes the child's cognitive, intellectual, and emotional development. It is part of human behavior and the culture of each society. The general objective is to determine the importance of play, and the specific objectives are to identify the advantages, analyze them, and describe them. Looking for the information according to the dependent and independent variables was essential. It allowed for the expansion of the study information. The research's methodology refers to a qualitative approach with a non-experimental design. The type of research is bibliographical and exploratory; consequently. It is a transversal study since the researcher gathered information in fieldwork for a specific period with the institution's students. The study involved 28 students, and the observation technique was applied using an observation sheet. It was also vital to conduct a questionnaire as the teacher's instrument. The researcher analyzed and interpreted the results obtained. Therefore, the conclusions and recommendations are related to the results obtained from the dependent and independent variables. The final results showed that children's game and its methodology are important for students' learning as it allows for cognitive and social skills development. It helps enhance their imagination and creativity, fostering innovation in decision making. It is advisable to implemen